Chlamydial infection of the male urethra. Issue 1 (February 1976) - Oriel, J D; Reeve, P; Wright, J T; Owen, J
Abstract : Urethral specimens from 477 men were collected with endourethral swabs and examined for Chlamydia trachomatis by cell culture on McCoy cells pretreated with idoxuridine. Of these men, 141 had gonococcal urethritis, 262 non-gonococcal urethritis (NGU), and 74 showed no evidence of urethritis. Of 118 men with heterosexually acquired gonococcal urethritis, thirty (25 per cent.), and of 23 men with homosexually acquired gonococcal urethritis, five (22 per cent.), yielded C. trachomatis from the urethra. Urethral specimens from 240 heterosexual men with NGU were examined, and 118 (49 per cent.) yielded C. trachomatis. Of these 240 men, 140 gave a past history of gonococcal or nongonococcal urethritis and 67 (48 per cent.) of these were positive for C. trachomatis; no past history was given by 100 men, of whom 51 were positive for C. trachomatis. Of the 240 heterosexual men with NGU, 81 had had symptoms for 7 days or more before examination, of whom 48 (59 per cent.) yielded isolates of C. trachomatis, and 145 had had symptoms for less than 7 days, of whom 59 (41 per cent.) yielded isolates. Of fourteen asymptomatic men, three were positive for C. trachomatis. Of 22 homosexual men with NGU, seven (32 per cent.) yielded C. trachomatis. C. trachomatis was recovered from the urethra in three (5 per cent.) of sixty heterosexual men without urethritis, and none of fourteen homosexual men without urethritis yielded C. trachomatis.